Adiabatic tapered optical fiber fabrication in two step etching. (January 2016) - Chenari, Z.; Latifi, H.; Ghamari, S.; Hashemi, R.S.; Doroodmand, F.
Abstract: A two-step etching method using HF acid and Buffered HF is proposed to fabricate adiabatic biconical optical fiber tapers. Due to the fact that the etching rate in second step is almost 3 times slower than the previous droplet etching method, terminating the fabrication process is controllable enough to achieve a desirable fiber diameter. By monitoring transmitted spectrum, final diameter and adiabaticity of tapers are deduced. Tapers with losses about 0.3 dB in air and 4.2 dB in water are produced. The biconical fiber taper fabricated using this method is used to excite whispering gallery modes (WGMs) on a microsphere surface in an aquatic environment. So that they are suitable to be used in applications like WGM biosensors. Highlights: A two-step etching method is proposed to fabricate adiabatic tapered fibers. The method provides a precise control over achieving a desirable diameter of the taper. The process is controlled by monitoring fiber optic transmission. A relation between final diameter and power transmission is shown. The fabricated ABFTs are efficient couplers to excite WGMs in aqua environment.